Estrogenic activity of a hydro-alcoholic extract of Bambusa arundinaceae leaves on female wistar rats - Talha Jawaid; Akanksha Awasthi; Mehnaz Kamal (Wolters Kluwer Medknow Publications, 2015)
To study the estrogenic activity of the hydro-alcoholic extract of Bambusa arundinaceae leaves (HEBA) in female Wistar rats. The dried powdered leaves were extracted with hydroalcoholic mixture (60%), and the resultant extract was subjected for phytochemical analyses to identify different phytoconstituents. HEBA were administered to ovariectomized rats for 7 days at three different doses (viz., 200, 300, 400 mg/kg body weight, p.o.) and their estrogenic activity were compared with each of daily treatment with 0.2 mg/kg body weight, i.p. conjugated equine estrogen as a positive control or olive oil as a negative control. Estrogenic activity was evaluated by doing uterotropic assay, vaginal cytology and measurement of vaginal opening in female Wistar rats. Oral administration of HEBA in ovariectomized immature and mature female Wistar rats in a dose of 400 mg/kg b.w. resulted in significant increase in the uterine wet weight (in mg) (224.82 ± 7.01) and (912.25 ± 27.22) when compared with ovariectomized control rats (111.52 ± 3.17) and (506.67 ± 21.39). HEBA (400 mg/kg b.w., p.o.) treated rats, showing only cornified epithelial cells which was an indication of the presence of the estrogen and also showed 100% vaginal opening. It was observed that HEBA possess significant estrogenic activity at 400 mg/kg b.w., p.o. which was evident by uterotropic assay, measurement of vaginal opening, and histopathological changes.